Implementasi Ekstrakurikuler Rohani Islam dalam Mengembangkan Sikap Spiritual Siswa - Rahayu Astria, Dewinda; Naelia Rahmah, Eka (Attractive : Innovative Education Journal, 2024)
Extracurricular activities in schools that are engaged in the religius field, one of which is extracurricular Islamic spirituality with the aim of not only developing students’ interests and talents but also making students who have faith and noble character. The purpose of this study was to determine how the implementation of Islamic spiritual extracurricular activities in developing students’ spiritual attitudes at SMPN 2 Tangerang selatan. With research subjects totaling 7 informants, including the Principal, PAI Teacher, Rohis extracurricular coach, and 4 students.This research is descriptive qualitative research, also data collection techniques using observasion, documentation and interview methods. The analysis technique uses data collection, data reduction, data presentation and conclution drawing. The results of this study indicate that the implementation of Islamic Spiritual extracurricular activities carried out at SMPN 2 South Tangerang is based on aspects of extracurricular steps, namely starting from planning activities, then implementin activities, to evaluating the results of activities are going well. Keywords: Extracurricular, Islamic Spiritual, Spiritual Attitudes